The Effects of schema-building on the composition-writing Skills of an ESL grade school student a case study - Ilao, Rochelle A.; Yanilla-Aquino, Lalaine F. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2012)
This study aimed to determine the effects of schema-building on an ESL grade school student's writing skills. It was hypothesized that schema-building would have a positive effect on the writing skills of the participant. The experimental case study involved one grade school participant who was tasked to undergo 30 hours of schema-building activities. The participant was tasked to write on three different topics and genres. A pre-test was given in order to measure the baseline writing skills. After the pre-test, the participant underwent 9 hours of schema building activities and then wast asked to do the middle-test--after which, another set of 21 hours of schema-building activities was given. After the schema-building activities, a post-test was given. The nine compositions written by the participant were analyzed using the Analytical Marking Scheme adapted from Leeand Paulson's Evaluation Criteria for Composition and Van Patten's Making Communicative Teaching Happen. Rubrics were used for evaluating the content, organization, vocabulary, grammar, and mechanics of the written compositions. The results of the data analysis showed that the schema-building activities had a positive effect on the participant's writing skills as seen in the improvement of the content, organization, vocabulary, grammar, and mechanics of the composition written as part of the post-test. It is recommended that schema-building be used un improving the other macro skills of ESL students - listening, speaking, and reading and be tried in a larger scale, such as with a small class of grade school students.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.